6th AIAA Atmospheric and Space Environments Conference 2014
DOI: 10.2514/6.2014-2614
|View full text |Cite
|
Sign up to set email alerts
|

Validation of 3-D Ice Accretion Measurement Methodology for Experimental Aerodynamic Simulation

Abstract: Determining the adverse aerodynamic effects due to ice accretion often relies on dry-air wind-tunnel testing of artificial, or simulated, ice shapes. Recent developments in iceaccretion documentation methods have yielded a laser-scanning capability that can measure highly three-dimensional features of ice accreted in icing wind tunnels. The objective of this paper was to evaluate the aerodynamic accuracy of ice-accretion simulations generated from laser-scan data. Ice-accretion tests were conducted in the NASA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 19 publications
3
40
0
1
Order By: Relevance
“…Although the PolyJet method was capable of manufacturing layers of this height, its tolerance was greater than the roughness height. This was verified by the aerodynamic results shown in Broeren et al 12 that showed that the maximum lift coefficients of the SLA and PolyJet ice shapes were 6% and 11% higher than the cast shape. Figure 26 shows the comparison plots for the rime ice accretion from run ED1977.…”
Section: Figure 23 Roughness Deviation Map -Ed1974supporting
confidence: 82%
See 2 more Smart Citations
“…Although the PolyJet method was capable of manufacturing layers of this height, its tolerance was greater than the roughness height. This was verified by the aerodynamic results shown in Broeren et al 12 that showed that the maximum lift coefficients of the SLA and PolyJet ice shapes were 6% and 11% higher than the cast shape. Figure 26 shows the comparison plots for the rime ice accretion from run ED1977.…”
Section: Figure 23 Roughness Deviation Map -Ed1974supporting
confidence: 82%
“…Artificial ice shapes were also constructed using the traditional mold/casting methods for both geometric and aerodynamic comparisons. The results of the aerodynamic comparison between the RPM shapes and the cast shapes are included in a companion paper by Broeren et al 12 This paper presents the results and analysis of the geometric comparison between the RPM shapes and the cast shapes.…”
Section: Table 2 Properties Of Rapid Prototype Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The digital scans were processed and used to make RPM ice shapes to compare to the castings. A total of six ice shapes were replicated and are discussed by Broeren et al, 5 although only two of these were tested with PSP. This further testing with PSP was used to help resolve observed aerodynamic differences between the castings and RPM shapes for a horn shape ( Fig.…”
Section: A Ice Shape Acquisitionmentioning
confidence: 99%
“…The aerodynamic performance validation results are presented and analyzed by Broeren et al, 5 who concluded that the 3-D laser scanner method was valid for most of the ice shape classifications tested. However, they found that the aerodynamics for a horn shape and a fine roughness shape generated from the new method did not satisfactorily agree with the respective casting aerodynamics.…”
Section: Introductionmentioning
confidence: 99%